Estimates of the Heritability of Human Longevity Are Substantially Inflated due to Assortative Mating. Issue 3 (31st October 2018) - Ruby, J Graham; Wright, Kevin M; Rand, Kristin A; Kermany, Amir; Noto, Keith; Curtis, Don; Varner, Neal; Garrigan, Daniel; Slinkov, Dmitri; Dorfman, Ilya; Granka, Julie M; Byrnes, Jake; et al.
Abstract: Here, Ruby et al. analyze an unprecedented amount of public family tree data from Ancestry and determine that the heritability of human longevity was well below 10%, lower than the widely-held belief that lifespan... Human life span is a phenotype that integrates many aspects of health and environment into a single ultimate quantity: the elapsed time between birth and death. Though it is widely believed that long life runs in families for genetic reasons, estimates of life span "heritability" are consistently low (∼15–30%). Here, we used pedigree data from Ancestry public trees, including hundreds of millions of historical persons, to estimate the heritability of human longevity. Although "nominal heritability" estimates based on correlations among genetic relatives agreed with prior literature, the majority of that correlation was also captured by correlations among nongenetic (in-law) relatives, suggestive of highly assortative mating around life span-influencing factors (genetic and/or environmental). We used structural equation modeling to account for assortative mating, and concluded that the true heritability of human longevity for birth cohorts across the 1800s and early 1900s was well below 10%, and that it has been generally overestimated due to the effect of assortative mating.